Peningkatan Hasil Belajar Tematik Terpadu Menggunakan Model Kooperatif Team Games Tournament di Sekolah Dasar - Wulandari, Tenti; Hamimah, Hamimah (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
This study aims to describe the use of the Team Games Tournament (TGT) type of cooperative model to improve student learning outcomes in integrated thematic learning in class IV SDN 11 Aur Kuning, Bukittinggi. This research is a classroom action research (CAR) that uses a qualitative and quantitative approach and is carried out in two cycles with three meetings consisting of four stages, namely planning, implementing, observing, and reflecting. The subjects of this study were the teacher and grade IV students totaling 26 students. The results showed an increase in the assessment of RPP in the first cycle was 76.78% increased in the second cycle to 92.85%. The implementation of the activities of the teacher in the first cycle was 77.26%, increasing in the second cycle to 90.90%. The implementation of the activities of the students in cycle I was 77.27%, increasing in cycle II to 90.90% and in the learning outcomes of students in cycle I was 66.8 increasing in cycle II to 84.28. It can be concluded that the cooperative model Team Games Tournament (TGT) type can improve student learning outcomes in integrated thematic learning in elementary schools.